Effect of Udvartan to Promote the Beauty w.s.r. to Skin-A Review - Patel, Namita; Sharma, Kamlesh Kumar (International Research Journal of Ayurveda & Yoga, 2022)
The skin means to help, including protection, excretion, expression, appearance, regulation, and sensation, among others. It also plays an important role in the recording of history. It is treated as a specialty in modern medicine. Ayurveda must recognise the necessity of the hour to identify not only skin ailments caused by modern lifestyles, but also other ailments. Happiness, melancholy, grief, and relaxation, according to Ayurveda, are elements that are expressed by the face and body and cannot be hidden with cosmetics. Ayurveda, in other words, puts a focus on both visible and internal attractiveness. Ayurveda believes that by knowing and practicing the basic principles of Ayurveda, one can improve one’s interior beauty. In Ayurveda, there is a secret beauty or the third dimension of beauty, which is also known as "self-realization." A self realized individual is thought to be perpetually attractive and does not require the usage of external cosmetics or expensive clothing. The therapies, treatments, and suggestions in Ayurveda, on the other hand, are concerned with physical beauty, which is thought to be the way to the secret of beauty. In Ayurveda, health promotion, beauty management, and healing are based on removing Ama (toxins), restoring cellular nutrition, promoting full elimination, and restoring Dosha balance. In this article, Basics about quality of skin & factors responsible for it including Prakruti; its maintenance with Udvartana.